THE EFFECTIVENESS OF WEB-BASED LEARNING ON THE STUDENTS’ MOTIVATION AND ABILITY IN WRITING NARRATIVE TEXT - Nur Rahmadani; Nurhaeni Nurhaeni (Intensive Journal, 2023)
In English, there are four skills which must be mastered, they are listening, speaking, reading, and writing. One of the language skills is writing that important for learners to practice their capability and their understanding, how to send ideas, and how to arrange words well. The objectives of this study were students’ motivation and ability to write narrative text who are taught through web-based learning, the writing motivation and ability of students who are not taught through web-based learning and to find out whether or not there is a significant effect of web-based learning to the students' motivation and ability to write narrative text for tenth-grade students of senior high school. The research was conducted at Muhammadiyah Boarding School in Prambanan Yogyakarta. This study used experimental research with nonrandomized-groups pre-test post-test control group design as the research design. The data were collected by using tests and questionnaires in the form of pre-test and post-test. The result of inferential analysis, showed by the result of the t-test, was found that the value of the ttable (2.001) was lower than the tobtained (3.532). Thus, H0 is rejected and H1 is accepted. It means that web-based learning had a significant effect on improving students’ writing motivation and ability.